Subjective health complaints in older adolescents are related to perceived stress, anxiety and gender – a cross-sectional school study in Northern Sweden - Wiklund, Maria (BioMed Central, 2012)
BACKGROUND: Negative trends in adolescent mental and subjective health are a challenge to public health work in Sweden and worldwide. Self-reported mental and subjective health complaints such as pain, sleeping problems, anxiety, and various stress-related problems seem to have increased over time among older adolescents, especially girls. The aim of this study has therefore been to investigate perceived stress, mental and subjective health complaints among older adolescents in Northern Sweden. METHODS: Data were derived from a cross-sectional school-based survey with a sample consisting of 16–18 year olds (n = 1027), boys and girls, in the first two years of upper secondary school, from different vocational and academic programmes in three public upper secondary schools in a university town in northern Sweden. Prevalence of perceived stress, subjective health complaints, general self-rated health, anxiety, and depression were measured using a questionnaire, including the Hospital Anxiety and Depression Scale (HADS). RESULTS: A large proportion of both girls and boys reported health complaints and perceived stress. There was a clear gender difference: two to three times as many girls as boys reported subjective health complaints, such as headache, tiredness and sleeping difficulties and musculoskeletal pain, as well as sadness and anxiety. High pressure and demands from school were experienced by 63.6% of girls and 38.5% of boys. Perceived stress in the form of pressure and demands correlated strongly with reported health complaints (r = 0.71) and anxiety (r = 0.71). CONCLUSIONS: The results indicate that mental and subjective health complaints are prevalent during adolescence, especially in girls, and furthermore, that perceived stress and demands may be important explanatory factors. Future studies should pay attention to the balance between gender-related demands, perceived control and social support, particularly in the school environment, in order to prevent negative strain and stress-related ill-health. The gender gap in subjective adolescent health needs to be further explored.